Parameterisation of a biodiesel plant process flow sheet model. (5th December 2016) - Sikorski, Janusz J.; Brownbridge, George; Garud, Sushant S.; Mosbach, Sebastian; Karimi, Iftekar A.; Kraft, Markus
Abstract : Highlights: A process flow sheet of a biodiesel plant is described with two types of surrogate models: polynomial and high-dimensional model representation (HDMR). Third order polynomial and HDMR surrogates achieve best and similar degree of accuracy. Polynomials of order higher than 3 suffer from overfitting, especially in high-dimensional scenarios. Global sensitivity analysis indicates that interaction terms have negligible effect on heat duties of the biodiesel plant. Abstract: This paper presents results of parameterisation of typical input–output relations within process flow sheet of a biodiesel plant and assesses parameterisation accuracy. A variety of scenarios were considered: 1, 2, 6 and 11 input variables (such as feed flow rate or a heater's operating temperature) were changed simultaneously, 3 domain sizes of the input variables were considered and 2 different surrogates (polynomial and high dimensional model representation (HDMR) fitting) were used. All considered outputs were heat duties of equipment within the plant. All surrogate models achieved at least a reasonable fit regardless of the domain size and number of dimensions. Global sensitivity analysis with respect to 11 inputs indicated that only 4 or fewer inputs had significant influence on any one output. Interaction terms showed only minor effects in all of the cases.